1994
DOI: 10.1104/pp.105.3.815
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Temperature-Sensitive Mutants of Arabidopsis thaliana That Are Defective in the Redifferentiation of Shoots

Abstract: Three temperature-sensitive mutants of Arabidopsis thaliana that were defective in the redifferentiation of shoots were isolated as tools for the study of organogenesis. Plasticity is a key feature of cytodifferentiation in higher plants. In response to phytohormones and/or wounding, various types of mature, differentiated plant cells are reactivated so that they acquire organogenic competence and then proliferate to form shoots, roots, or somatic embryos. Physiological, biochemical, and molecular biological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 14 publications
1
45
0
2
Order By: Relevance
“…More importantly, the efficiency of shoot induction obtained in the proposed IZE-based protocol is similar to that reported in seedling root culture (Feldman and Marks, 1986), which thus far has been the one most frequently employed in genetic studies on regeneration induced in vitro (Yasutani et al, 1994;Banno et al, 2001;Zhao et al, 2002;Daimon et al, 2003). In both of these systems, IZE and root-derived, a sequence of two media with opposite auxin-to-cytokinin ratios results in de-differentiation of primary explant tissue and subsequent shoot induction during 3-week culture.…”
Section: Discussionsupporting
confidence: 58%
“…More importantly, the efficiency of shoot induction obtained in the proposed IZE-based protocol is similar to that reported in seedling root culture (Feldman and Marks, 1986), which thus far has been the one most frequently employed in genetic studies on regeneration induced in vitro (Yasutani et al, 1994;Banno et al, 2001;Zhao et al, 2002;Daimon et al, 2003). In both of these systems, IZE and root-derived, a sequence of two media with opposite auxin-to-cytokinin ratios results in de-differentiation of primary explant tissue and subsequent shoot induction during 3-week culture.…”
Section: Discussionsupporting
confidence: 58%
“…Previously, we characterized temperature-sensitive mutants of A. thaliana to dissect the process of shoot and root regeneration via callus formation (Yasutani et al, 1994;Ozawa et al, 1998;Sugiyama, 2003). Here we extend this approach to elucidate the process of adventitious root formation.…”
Section: Introductionmentioning
confidence: 99%
“…was used as the wild type. The srd2 mutant of Ler origin, which was isolated as temperature-sensitive for shoot redifferentiation (Yasutani et al, 1994) and later also shown to be defective in dedifferentiation and root development (Ozawa et al, 1998), was used together with newly isolated mutants. The scarecrow-2 (scr-2) mutant in the Wassilewskija background (Scheres et al, 1995) and the microtubule organization 1-1 (mor1-1) mutant in the Columbia background (Whittington et al, 2001) were kindly provided by Dr Ben Scheres (Utrecht University, The Netherlands) and Dr Geoffrey O. Wasteneys (The Australian National University, Australia), respectively.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Munetaka Sugiyama and colleagues established an experimental system suitable for studying callus, root, and/or shoot induction from Arabidopsis explants (Yasutani et al 1994;Ozawa et al 1998). Using this system, they isolated and characterized many mutants, which led to the identification of genes involved with dedifferentiation and also in organogenesis.…”
Section: Study Of Organogenesis In Arabidopsismentioning
confidence: 99%